2005
DOI: 10.1159/000081777
|View full text |Cite
|
Sign up to set email alerts
|

Fixation Stability and Macular Light Sensitivity in Patients with Diabetic Maculopathy: A Microperimetric Study with a Scanning Laser Ophthalmoscope

Abstract: Background: In patients with diabetic maculopathy, evaluation of visual acuity alone may not represent central retinal function sufficiently. Despite good visual acuity, patients may suffer from visual disturbances like waviness, relative scotoma, loss of fixation and decrease of contrast sensitivity. The aim of the study was to assess localized light sensitivity in the central visual field and to determine fixation stability in patients with diabetic maculopathy with moderate visual loss in comparison to heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 30 publications
7
35
2
1
Order By: Relevance
“…Such an observation was confirmed by previous studies of eyes with DME and UME. [18][19][20] Our findings were in contrast with some of the other reports. 15,21 Roesel et al 21 showed a correlation between retinal sensitivity measured with the MP1 (Nidek Technologies, Padova, Italy) and BCVA measured by the ETDRS chart in eyes with UME.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Such an observation was confirmed by previous studies of eyes with DME and UME. [18][19][20] Our findings were in contrast with some of the other reports. 15,21 Roesel et al 21 showed a correlation between retinal sensitivity measured with the MP1 (Nidek Technologies, Padova, Italy) and BCVA measured by the ETDRS chart in eyes with UME.…”
Section: Discussioncontrasting
confidence: 99%
“…[12][13][14] Recently, microperimetry has added in-depth quantification of the function of the macula and has provided detailed information about the degree and pattern of retinal alteration in the course of edema. 1,2,15,18,19 The integrated automated fundus perimetry/tomography and SD-OCT module of the Spectral OCT/SLO system has allowed an in-depth and more accurate evaluation of both retinal anatomy and corresponding function, with novel findings about their relationship as well as with associated factors. In our current study, we have measured the retinal thickness and sensitivity using the Spectral OCT/SLO device, which is an automatic, simultaneous fundus perimetry/ tomography system, with a microperimetric circular pattern to cover the central 1 mm of the fixation center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] In our study, consistent with previous studies, a significant decrease in mean light sensitivity was also found. Retinal sensitivity and stability of fixation in CSME were reported to be reduced compared with normal values.…”
Section: Discussionsupporting
confidence: 93%
“…This decrease is mostly due to a localized loss of light sensitivity in areas with severe tissue alteration and to a lesser extent due to diffuse loss of light sensitivity. 9 Fixation characteristic are critical for many visual tasks like reading. Variations of size, shape, and intensity of scotoma greatly influence visual performance.…”
Section: Discussionmentioning
confidence: 99%